Diagnostic and Therapeutic Considerations Towards Dientamoeba fragilis in Children: A Survey Amongst General Practitioners and Pediatricians in the Netherlands. Issue 6 (13th December 2021) - van Kalleveen, Michael W.; van Bergen, Merel; Benninga, Marc A.; Savelkoul, Paul H.M.; Plötz, Frans B.; de Meij, Tim G.J.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: This survey was undertaken to obtain insight in the attitude of Dutch physicians towards pathogenicity, diagnostic- and therapeutic approach towards Dientamoeba fragilis in children. Physicians were invited by e-mail for a questionnaire. A total of 211 of 450 physicians (46.9%) completed the questionnaire, including 67 general practitioners (GPs) and 144 pediatricians. Of all respondents, 175 of 211 (82.9%) considered D fragilis a "potential pathogen", when other causes of gastro-intestinal complaints are ruled out. Only 16 of 211 (7.6%) performed diagnostic tests regularly. Diagnostic tests were performed by 162 of 211 (77%) of respondents in children with diarrhea and abdominal pain in consideration of duration of symptoms. Fecal polymerase chain reaction (PCR) was diagnostic modality of preference. Eighty-nine of 142 (62.7%) prescribed metronidazole as antibiotic of first choice. This study shows heterogeneity in clinical practice amongst Dutch physicians regarding diagnostic- and therapeutic approach of D fragilis in children. Different attitude towards pathogenicity and inconsistent guidelines could be causative factors.